Women Entrepreneurs as Change Leaders: Overcoming Barriers and Driving Economic Growth - Rahma Kartika; Indah Puspitasari; Dian Anggraini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores the experiences of women entrepreneurs as change leaders, focusing on their contributions to economic growth and the barriers they encounter. By analyzing case studies from diverse industries, the research identifies strategies for overcoming challenges such as limited access to funding, mentorship, and restrictive societal norms. The findings emphasize the importance of fostering inclusive leadership and supportive ecosystems to unlock the full potential of women entrepreneurs.